Implementing the Alumni-Unicamp platform: A case study - Kassisse, Dora Maria Grassi (ICAReAlumni Conference Proceedings, 2023)
Background and objectives: Unicamp is a young university, currently comprising about 20,000 undergraduate students, 18,000 in graduate school and almost 3,000 in high school. It trains around 2,500 undergraduates per year, with the same number of postgraduate graduates and around 1,100 high school graduates. Previous experiences for the creation and maintenance of a platform for Unicamp graduates were not perennial due to the high maintenance cost and the need for people directly linked to the program. In this way, this project was designed with the aim of connecting graduates and students in training with the possibility of direct interactions, such as offering internships and/or mentorships, and in exchange keeping up to date on courses, participation in structuring teaching centers, in events at Unicamp and much more. Process: The intention to keep in touch with the former community goes beyond the need to fill in rankings. This project aimed to include all graduates on a single platform, allowing for general communication and also in groups separated by courses or even classes. It belongs to Pro-Rectory of Undergraduate Studies, and the partnership of the Center for Computing and Coordination of Information Technology, the directory of academic board and the advice of the dean's office were essential to the success of the actual program. Outcomes and impact: The customization of our Alumni platform, hosted today at: https://unicamp-alumni.org.br/feed, was carried out. The launch took place in August 2020, and in March 2021 we had 5 thousand members. The continuous and careful action of the team ensured security in the system and feed publications, ease of access and in the dissemination of vacancies. This project was thought of, idealized and executed at no cost in the PRG Planes budget. Conclusion: The project meets immediate and future expectations, shows replicability, efficiency, and cost and time reduction. However, we still need the supervisors to achieve that at least 10% of our 150,000 users were fed into the system by the Academic Board.